2016
DOI: 10.1016/j.envint.2015.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to black carbon, cognition and single nucleotide polymorphisms in microRNA processing genes in older men

Abstract: Introduction Air pollution exposure has been linked to impaired cognitive aging, but little is known about biomarkers modifying this association. MicroRNAs (miRNAs) control gene expression and neuronal programming. MiRNA levels vary due to single nucleotide polymorphisms (SNPs) in genes processing miRNAs from precursor molecules. Objectives To investigate whether SNPs in miRNA-processing genes are associated with cognition and modify the relationship between black carbon (BC), marker of traffic-related pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Indeed, several miRNAs target BACE1, including miR-9, miR-29, miR-107, miR-186, miR-188, miR-298, and miR-328, some of which are closely related to synaptic and cognitive function [ 40 , 41 ]. A recent study reported that long-term exposure to black carbon was linked to cognitive status due to influences on miRNA expression [ 79 ]. However, little is known regarding whether miRNAs aggravate synaptic and cognitive dysfunction by elevating the expression of BACE1 following PM 2.5 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several miRNAs target BACE1, including miR-9, miR-29, miR-107, miR-186, miR-188, miR-298, and miR-328, some of which are closely related to synaptic and cognitive function [ 40 , 41 ]. A recent study reported that long-term exposure to black carbon was linked to cognitive status due to influences on miRNA expression [ 79 ]. However, little is known regarding whether miRNAs aggravate synaptic and cognitive dysfunction by elevating the expression of BACE1 following PM 2.5 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…We selected PM 2.5 and BC as our ambient particle exposures because of their global pervasiveness [1] in addition to their status as the leading ambient particles with well-documented relationships with both DNA methylation [5355] and adverse health outcomes [5659]. …”
Section: Methodsmentioning
confidence: 99%
“…Regarding the potential role of miRNAs in the effects of PM on CNS function, long-term exposure to BC was shown to be associated with cognitive impairment in older men, which was also associated with SNPs in miRNA processing genes (27).…”
Section: Mirnas and Heavy Metalsmentioning
confidence: 99%